Caminhos do mundo, espaços e almas a conquistar: frades alemães no Brasil - Melo, Taciana Santiago de (2016)
From 1891, Franciscans from Germany landed in the Brazilian territory in order to save the existence of the Order in the country and prevent it from an imminent extinction. From the end of the 19'' century and during the 20e' century, these friars left an important heritage Brazil that covers not only lhe religious and missionary fields, but also the social and cultural areas, including Architecture and Urbanism. Inspired by a practical mentality linked to wodt, the German friars undertook a sedes of renovations in the old colonial Brazilian friaries that helped the preservation of these buildings until the present, even though, in some cases, they had faced conflicts with these spaces; they reached large cities, tiny cities and also forests, expanding the Franciscan activity to the inland parts of the country; they built new churches and Maltes that had an important role in lhe development of cities that started to grow in lhe end of the 19m century. This still little known history will be the main topic of this work, that MI rely on other time frames ár order to carry out an analysis about the actions of the German Mars in Brazil and its resulta in the space. It will be used as a support, in particular, the History of the Order in the Middle Ages, since the franciscanism arose in this period as a religious model that had strong emphasis in the material world. lhe use of written documents, especially the primary sources, and the experience in the studied localities through the technical visits made to Italy, Germany and three different regions of Brazil, were the main methodological toais used ia this dissertation. At a first moment, the work focused on the ways that Saint Francis and the franciscanism had built their memodes in the tangible world. In view of this approach, lhe research bied to understand this process in Brazil, focusing on the period in which the German friars had a strong influence in the country. Therefore, the dissertation aimed to investigate the motivations and effects of the action and legacy of these friars in the Brazilian territory, using as study guide the relationship between the franciscanism, materiality and itinerancy.